2020
DOI: 10.1111/jth.14991
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of prothrombin complex concentrate for the treatment of bleeding: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 46 publications
(171 reference statements)
5
26
0
3
Order By: Relevance
“…To date, several observational studies and a single randomized pilot study have compared the use of PCC with FP in cardiac surgery. 13 , 23 Although the observational studies are heterogeneous, meta-analyses of their results suggest that PCC is associated with decreased blood loss and red cell transfusions, 13 , 23 which is consistent with the findings of our study. The meta-analyses also explored the safety of PCC and found no association with thromboembolic adverse events, but did note a trend toward increased risk of kidney dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…To date, several observational studies and a single randomized pilot study have compared the use of PCC with FP in cardiac surgery. 13 , 23 Although the observational studies are heterogeneous, meta-analyses of their results suggest that PCC is associated with decreased blood loss and red cell transfusions, 13 , 23 which is consistent with the findings of our study. The meta-analyses also explored the safety of PCC and found no association with thromboembolic adverse events, but did note a trend toward increased risk of kidney dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Pharmaceutic hemostatic agents such as fibrinogen concentrate and PCC have been widely incorporated into current therapeutic algorithms for the treatment of massive hemorrhage in trauma patients, intraoperatively, and in cases of obstetric hemorrhage [ 35 , 36 ]. Their use is widespread in many countries and numerous studies have demonstrated their clinical benefits over FFP [ 37 , 38 , 39 ]. The low rate of use of hemostatic agents recorded in our study may not reflect the true picture, since the provision of these agents may not be carried out exclusively through BTSs.…”
Section: Discussionmentioning
confidence: 99%
“…However, to what extent these parameters are influenced by thrombin generation or substrates such as fibrinogen or platelets remains to be elucidated. Importantly, the use of prothrombin complex concentrate in bleeding patients does not come without significant side effects and has been associated with rates of up to 41% of thromboembolic events [18].…”
Section: Introductionmentioning
confidence: 99%